2019
DOI: 10.1186/s12876-019-1140-8
|View full text |Cite
|
Sign up to set email alerts
|

Danaparoid sodium-based anticoagulation therapy for portal vein thrombosis in cirrhosis patients

Abstract: BackgroundPortal vein thrombosis (PVT) is a common complication of cirrhosis. However, in patients with PVT and cirrhosis, there is no clear evidence supporting effective treatment modalities. In this study, we examined the effectiveness and safety of anticoagulation therapy using danaparoid sodium for PVT in patients with cirrhosis.MethodsThis retrospective study assessed 52 cirrhotic patients with PVT treated with danaparoid sodium for 2 weeks between November 2008 and September 2018. The primary outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…An analysis was performed in those two groups to investigate the correlation factors that affected treatment efficacy. However, this analysis also indicated no significant difference in the correlation factors: the Child–Pugh score, ALBI score, FIB-4 index, plasma AT-III level (this date has been presented in our previous report [ 19 ]), plasma FDP level, plasma DD level, blood platelet count, plasma PT activity, or pretreatment PVT volume ( Figure 3 ). In addition, serum albumin level and total serum bilirubin also revealed no significant difference ( Supplementary Figure S1 ).…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…An analysis was performed in those two groups to investigate the correlation factors that affected treatment efficacy. However, this analysis also indicated no significant difference in the correlation factors: the Child–Pugh score, ALBI score, FIB-4 index, plasma AT-III level (this date has been presented in our previous report [ 19 ]), plasma FDP level, plasma DD level, blood platelet count, plasma PT activity, or pretreatment PVT volume ( Figure 3 ). In addition, serum albumin level and total serum bilirubin also revealed no significant difference ( Supplementary Figure S1 ).…”
Section: Resultssupporting
confidence: 55%
“…There are several reports in which patients received anticoagulant treatment for at least 6 months [ 20 , 21 ]. On the other hand, previous studies conducted in Japan have reported treatment efficiency with short-term administration of danaparoid sodium for only 2 weeks [ 15 , 19 ]. The short duration of treatment is directly dependent on the health care system and social background of people in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Main characteristics of studies are summarized in Table 1. The sample size ranged from 16 [14,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and 14 as abstracts [38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Included Studiesmentioning
confidence: 99%